Synergistic Effect of Graphene and Boron Nitride on the Electrical Conductivity and Mechanical Properties of Hybrid Polymer Composites - Ramesh Gajula; Singh Rajat; Singh Jaskirat; Vafaeva Khristina Maksudovna; Gupta Tannmay; Singh Sandeep (E3S Web of Conferences)
This work examines the combined influence of graphene and hexagonal boron nitride (h-BN) on the electrical conductivity, mechanical characteristics, and thermal stability of polyvinylidene fluoride (PVDF)-based hybrid polymer composites. Graphene and h-BN were exfoliated and amalgamated in different ratios (1:1, 2:1, and 3:1), thereafter integrated into the PVDF matrix at nanofiller concentrations of 0.5 wt%, 1.0 wt%, 2.0 wt%, and 5.0 wt%. Mechanical tests demonstrated substantial improvements in tensile strength and Young’s modulus, especially for composites with a 2:1 graphene-to-h-BN ratio. Electrical conductivity significantly enhanced with increasing nanofiller content, reaching a peak of 5.0 × 10⁻² S/m at a 5.0 wt% nanofiller concentration with a 3:1 graphene-to-h-BN ratio. Thermal stability has also improved with degradation temperatures increased by up to 70°C more as compared to PVDF. The findings demonstrate that the ideal nanofiller structure (2:Adding one graphene ratio at 5.0 wt% strikes a balance of these properties enabling the composites to be applied in electronics, sensors, and advanced structures